Visual Communication Design for Promoting Pindang Borgibor as a Culinary Heritage of South OKU in Palembang City, Indonesia - Hediana Imelda Edwar; Husni Mubarat; Yosef Yulius (Manunggal Halim Jaya, 2026)
Pindang Borgibor is a traditional dish from South OKU, South Sumatra, combining freshwater fish with tempoyak-based sauce. Its popularity remains low, particularly among Generation Z in Palembang, who tend to prefer modern cuisine and digital lifestyle trends. This project aims to introduce Pindang Borgibor more effectively, with the expectation of increasing its appeal among Generation Z in Palembang. Additionally, this promotional effort seeks to support the preservation of local culinary heritage and contribute positively to the regional creative economy rooted in culinary culture. The design method employed is the Design Thinking approach, which consists of five key stages: empathize, define, ideate, prototype, and test. Data were collected through observations, interviews, surveys, and literature reviews related to traditional culinary promotion strategies. The project resulted in various forms of promotional media, including an innovative instant pindang product (Self Cooking Box), promotional videos, and visual print media, all designed to align with the information-consumption habits of Generation Z. Through a strong visual approach and the strategic use of social media, this initiative is expected to improve the recognition and appreciation of Pindang Borgibor, helping it become part of an evolving culinary identity while supporting cultural preservation and the growth of the regional culinary-based creative economy.